2021
DOI: 10.3889/oamjms.2021.7780
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Score Model of Clinical Outcomes Sepsis in Intensive Care Unit Tertier Referral Hospital of Eastern Indonesia

Abstract: AIM: This study aimed to design a predictive score model of clinical outcome sepsis and bacterial profiles of blood and sputum cultures in the intensive care unit (ICU) of a tertiary referral hospital. METHODS: An observational retrospective study was conducted in 2017–2020 using medical record data in the ICU of Dr. Soetomo Hospital as tertiary referral hospital. The predictor of sepsis prognosis was Acute Physiology and Chronic Health Evaluation II (APACHE II), blood and sputum culture results, procalciton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Of the Gram-negative bacteria, Enterobacteriaceae showed a proportion of 59%, followed by Acinetobacter baumannii at 29%. 12 The 43 E. coli strains isolated from the blood culture of BSI comprised 20 male patients and 23 females. This data aligns with a systematic literature review report that women were more likely than men to develop E. coli bacteremia overall.…”
Section: Resultsmentioning
confidence: 99%
“…Of the Gram-negative bacteria, Enterobacteriaceae showed a proportion of 59%, followed by Acinetobacter baumannii at 29%. 12 The 43 E. coli strains isolated from the blood culture of BSI comprised 20 male patients and 23 females. This data aligns with a systematic literature review report that women were more likely than men to develop E. coli bacteremia overall.…”
Section: Resultsmentioning
confidence: 99%
“…The Gram-negative bacteria group showed A. baumannii as the most common cause of sepsis. 28 Studies in the USA reported sepsis as the most common cause of death in critically ill patients with various types of organisms in culture-positive infected patients, with Gram-negative bacteria (62.2%) as the most causative types of causal organisms. Most microorganisms isolated from blood cultures in patients with Gram-negative bacteremia were Pseudomonas species (19.9%), E. coli (16%), Klebsiella species (12.7%), Acinetobacter species (8.8%), and Enterobacter (7.0%).…”
Section: Discussionmentioning
confidence: 99%
“…17 Another study evaluated the role of procalcitonin as the predictor of mortality, yet combining it with Acute Physiology And Chronic Health Evaluation II score, sputum culture interpretation, and blood culture interpretation. 28 Procalcitonin and lactate levels could be used as an evaluation tool for patients with sepsis. Procalcitonin was used to evaluate clinical conditions within 28/30 days of evaluation, yet still has limitations in predicting mortality.…”
Section: Discussionmentioning
confidence: 99%